Dental status changes in patients with ischemic heart disease and the ways of its normalization - Kravchenko, L. S.; Bas, N. O.; Aksynorska, O. I.; Herasymova, I. V.; Rozumenko, M. V.; Rozumenko, V. O. (Journal of Education, Health and Sport, 2020)
Aim: increasing the effectiveness of treatment of periodontal disease in patients with ischemic heart disease Materials and methods. The oral cavity was examined and the clinical course features of chronic periodontitis were studied in patients with ischemic heart disease Determing dental, hygienic index and biochemical indices in oral liquid (elastase, MDA, urease, lysozyme, catalase). The “Apifil” and “Asepta” were used by oral rinsing. Results. The patients with ischemic heart disease have a worse state of oral cavity, compared to those who do not suffer from ischemic heart disease. The determined periodontal indexs provided evidence of a significantly higher activity of the dystrophic and inflammatory changes of periodontal tissues in the patients with ischemic heart disease. The oral cavity liquid levels of elastase, urease were raised, but levels of catalase and lusozyme were reduced in patients with ischemic heart disease Oral rinsing of “Apifil” and “Asepta” were reduced the levels of elastase, urease and dental indices but were raised the levels of lysozyme and catalase. Conclusions. The rinse “Apifil” render the stomatoprotective action on patients with ischemic heart disease.